POSSIBILITIES OF CIRCUS ACTIVITIES IN PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2011)
This study aimed at investigating the limitations and possibilities of teaching circus activities in school physical education classes with 6th and 8th graders of Escola São Francisco de Assis, in Santa Teresa – Espírito Santo, Brazil. It is a qualitative study guided by some action research elements. We reflected on the role of the school in society, physical education in the school, and circus activities as physical education curricular content. We reported the experience acquired with these groups, pointed out difficulties/limitations and possibilities witnessed, and questioned students' resistance to curricular contents considered "innovative".
Keywords: physical education; school; circus activities